حفظانِ صحت کے متعلق والئی سوات کے فرامین کا شرعی و تحقیقی جائزہ - Saif Ullah; Lutfullah Saqib (Pakistan Journal of Islamic Research)
Being a complete code of life, Sharī’ah (Islamic law) provides a comprehensive guideline for the human being in every facet of life. Further, such unique legal system cares, too, about the health of all mankind – without any sort of discrimination on the basis of color, creed, religion etc. Many verses of the Holy Qurān and Ḥādīth   of the Holy Prophet (SM) confirm the same. While following this, Muslim rulers in every era have enforced the same guideline for the protection of health in their concerned territories.  Wali Swat (a famous ruler of Swat) did the same in the regime of swat.  It is believed, by some quarters, that such rules were the mixture of Sharī’ah, customs and British laws. The present study aims to find out and critically analyze whether such guideline, about health protection, are in line with the principles of Sharī’ah or these are a mixture of the three various sources- as stated earlier.  To investigate the issue, content analysis technique of qualitative research has been followed in the present work. Firstly, the legal verdicts of the regime of Wali Swat are presented one by one and then analyzed by the same way from the perspective of Sharī’ah. To do it appropriately, views of all Muslim jurists (fuqahā) are presented and argued to the best possible extent. However, the Hanfī school of thought is cited more comparatively to other schools as the same school is followed by the majority of people of the region.